Development of Interactive Flipbook-Based E-Module for Teaching Algorithms and Basic Programming in Higher Education - Rama Putra Mahendri; Mita Amanda; Ulfi Latifah; Soha Rawas (Sagamedia Teknologi Nusantara, 2023)
The COVID-19 pandemic has forced educational institutions to switch to online learning, which has posed challenges related to the lack of interactive digital teaching materials. Specifically, the available materials in the Algorithm and Basic Programming course are static and text-based, making it difficult for students to study independently. This study aims to develop an interactive digital book-based e-module with multimedia features to enhance student engagement and understanding and evaluate the quality and effectiveness of the e-module. The study used the 4D (Define, Design, Development, Disseminate) development model. The Define stage involved a needs analysis, while the Design stage included media selection, video preparation, and quiz development. The Development stage consisted of validation by three expert validators and limited trials with 30 students. Data analysis used descriptive methods by calculating the validation percentage and trial results. The validation results showed an eligibility of 89.00% for media and 88.33% for content, both in the